Capitanear la reconstrucción, organizar el trabajo forzado. El ingeniero Juan Petrirena, del Servicio de Colonias Penitenciarias Militarizadas a la fortificación de los Pirineos - Gorostiza, Santiago ; 0000-0002-8516-5642 (Rubrica Contemporanea, 2025)
Interdisciplinary dialogues between political history, environmental history, and the history of science and technology have significantly expanded in recent years. In this context, research on engineers as a key professional group in the material construction of the state has addressed both the political and material dimensions of their work, particularly during the Francoist dictatorship. However, these studies have paid little attention to the role of engineers in the organisation of forced labour. From the perspective of Perpetrator Studies, the organisation of forced labour can be interpreted as a form of perpetration of violence, in which engineers played a key role. Drawing on this approach, this article examines the trajectory of military engineer General Juan Petrirena Aurrecoechea (1885-1956), who served as head of the Servicio de Colonias Penitenciarias Militarizadas from 1939 and was responsible for overseeing the engineering works for the fortification of the Pyrenees between 1945 and 1951.
Publisher Copyright: © 2025, Universitat Autonoma de Barcelona. All rights reserved.
Keywords: Engineers; forced labour; fortification; Francoism; perpetrators; Pyrenees